Fragmentation of molecular ions in ultrafast laser pulses - Ablikim, Utuq (Kansas State University, 2015)
Imaging the interaction of molecular ion beams with ultrafast intense laser fields is a very powerful method to understand the fragmentation dynamics of molecules. Femtosecond laser pulses with different wavelengths and intensities are applied to dissociate and ionize molecular ions, and each resulting fragmentation channel can be studied separately by implementing a coincidence three-dimensional (3D) momentum imaging method. The work presented in this master’s report can be separated into two parts. First, the interaction between molecular ion beams and femtosecond laser pulses, in particular, the dissociation of CO[superscript]+ into C[superscript]++O, is studied. For that purpose, measurements are conducted at different laser intensities and wavelengths to investigate the possible pathways of dissociation into C[superscript]++O. The study reveals that CO[superscript]+ starts to dissociate from the quartet electronic state at low laser intensities. Higher laser intensity measurements, in which a larger number of photons can be absorbed by the molecule, show that the doublet electronic states with deeper potential wells, e.g. A [superscript]2Π, contribute to the dissociation of the molecule. In addition, the three-body fragmentation of CO[subscript]2[superscript]+ into C[superscript]++O[superscript]++O[superscript]+ is studied, and two breakup scenarios are separated using the angle between the sum and difference of the momentum vectors of two O[superscript]+ fragments. In the second part, improvements in experimental techniques are discussed. Development of a reflective telescope setup intended to increase the conversion efficiency of ultraviolet (UV) laser pulse generation is described, and the setup is used in the studies of CO[superscript]+ dissociation described in this report. The other technical study presented here is the measurement of the position dependence of timing signals picked off of a microchannel plate (MCP) surface. The experimental method is presented and significant time spread over the surface of the MCP detector is reported [1].
Keywords: Ultrafast lasers; Molecular Physics; CO+ dissociation; Microchannel plate detectors; CO2+ fragmentation; Physics (0605)